The Role of Green Marketing Mix and Green Brand Image on Purchasing Decisions of Sensatia Botanicals Nusa Tenggara - Fatana Suastrini; Muhammad Helmy Reza (Fundamental and Applied Management Journal, 2026)
This study aims to analyze the influence of green marketing mix and green brand image on purchasing decisions for Sensatia Botanicals products at the Nusa Tenggara branch in Mataram, Lombok, West Nusa Tenggara Province. This study used 385 respondents. The analysis method used to prove the research hypothesis is by using Structural Equation Modeling (SEM) analysis. The data analysis technique process using this method is assisted by the Microsoft Excel for Windows computer program and the Analysis of Moment Structure (AMOS) Version 22. The probability value (P) of the relationship between the green product variable and the purchasing decision is at a value of ≤ 0.05 with an estimate value of 0.471, which means that the green product variable has a positive and significant effect on the purchasing decision variable. The probability value (P) of the relationship between the green promotion variable and purchasing decisions is at a value of ≤ 0.05 with an estimate value of 0.367, which means that the green promotion variable has a positive and significant effect on the purchasing decision variable. The probability value (P) of the relationship between the green brand image variable and purchasing decisions is at a value of ≤ 0.05 with an estimate value of 0.336, which means that the green brand image variable has a positive and significant effect on the purchasing decision variable. Overall, the results indicate the green marketing mix variable and green brand image has a significant effect on purchasing decisions. One limitation of this research is that it focuses solely on Sensatia Botanicals products, so it cannot be applied directly to other products due to different consumer characteristics. In addition, this study only covers the area of Mataram City, Lombok Island, West Nusa Tenggara Province, so the results cannot be generalized to a wider population.